Delphi study to elicit expert consensus around decision-making in the treatment of Friedreich ataxia - Kuo, Sheng Han; Tian, Cuixia; McKay, James; England, Sarah M.; Simon, Monica; Graf, Marlon; Brewer, Iris P.; Land, Natalie; Chou, Jacquelyn W.; Lawson, Richard (Frontiers in Neurology, 2025)
IntroductionFriedreich ataxia (FA) is a rare neurological disease. This study aimed to understand current FA management and treatment practices among neurologists.MethodsAn online, modified Delphi study consisting of 34 United States (US)-based neurologists with varying levels of FA experience was conducted. The Delphi questionnaire consisted of likelihood, ranking, and parameter estimation questions related to FA decision-making practices. Data collection occurred in 3 sequential rounds: completion of Delphi questionnaire, webinar discussion, and re-completion of the questionnaire. Consensus was reached in Round 3 if the inter-quartile range [IQR] was ≤25 around the median group response [MED] (scaled 0–100) or if ≥75% of panelists ranked an option in the top-2. Results were analyzed for the full panel and separately for experienced FA-treaters.ResultsPanelists strongly agreed overlapping symptoms with other ataxic or neurologic conditions is a key diagnostic challenge (MED = 90, IQR = 1.7) with misdiagnosis being the most important driver in delayed FA diagnoses (MR = 1.7, 65% top-2). General neurological exams were the most frequently used tool to assess FA disease progression (MED = 100, IQR = 0) whereas panelists were largely unfamiliar with any of the clinical outcome assessment scales provided (MED range: 5–10, IQR range: 20–23). Experienced FA-treaters’ responses were largely consistent with the full panel; however, some differences were observed.DiscussionConsensus was reached on a portion of questions regarding FA diagnosis and assessment, perhaps due to the rarity of disease and panelists’ varying FA experience. To improve and standardize management of FA, it is important to establish best practices and educate potential FA treaters as new therapies emerge.